Regional Government Information System Policy in Seluma Regency (Study on the Regional Planning Agency of Seluma Regency) - Lorita, Evi; Kader, Bando Amin C; Wulandari, Selfia (Utan Kayu Publishing, 2023)
This study aims to decide to implement the Regional Government Information System (SIPD) in the Seluma Regency Development Planning Agency. Through data obtained from survey sites and information analysis. This study is a qualitative study presented descriptively. The information in this study consists of four informants. Data recording techniques use observation, interviews, and documents. Based on the findings of research and discussion using the theory of Edward III (Tresiana Duaji, 2019: 59), an indicator is used: 1) Communication: Backsel Marigen Recei and OPD/SKPD -SELUMA Government Communications Submission of OPD/SKPD information necessary for preparing developmental documents is also complete and clear. Information data is sent by entering information data through the Portal 1 Indonesia (SDI) data. 2) Resources: Backta Seluma Regency Resources are also very good and satisfactory. The operator's ability is qualified to operate SIPD, but due to the lack of BIMTEK training, there is a lack of other training programs for SIPD operators from Backta Seluma Regz, which is a sufficient SIPD operator from the APBD, is not properly turned on. 3) Disposal: The implementation of Bapteda Seluma Regency is sufficient, and the implementer already has a strong attitude and wants to implement SIPD in the preparation of regional development plan documents. Bureaucratic Structure: The bureaucratic structure in the implementation of SIPD directives is sufficient to accommodate standard operating processes (SOP).